AUTOMATION OF ENERGY LOSSES CALCULATION IN 10(6) kV DISTRIBUTIVE NETWORKS - Kutin, Vasyl; Kulyk, Volodymyr; Piskliarov, Dmytro; Lonska, Olena (Scientific Works of Vinnytsia National Technical University, 2015)
New approaches aimed at increase of efficiency of energy losses calculations methods in 10(6) kV distributive networks in conditions of partially indetermined initial information are suggested: methods of determinationt of group load graph form and evaluation coefficients of observability of distributive electric networks for problems of losses calculation are elaborated. The realization of observability evaluation algorithm within the context of the solution of the problem dealing with the implementation of computerbased system of commercial account of electric energy in distributive electric networks by means of programming complex “ВТРАТИ-110-0,4” (LOSSES-110-0,4 is shown).